Pola Komunikasi Organisasi Dalam Pengembangan Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Islam Negeri Raden Fatah Palembang - Hambali Hambali; Mutia Rahmadini (Jurnal Studi Sosial dan Politik, 2018)
Communication in organization is very necessary. Because if the organization without good communication, then the common goal will not be achieved. So that’s why, the effective and efficient communication systems are needed. Communication is not only can be done through verbal, but it also can be done through the writing. Based on the context above, the purpose of this research is to answer the question of how the Communications System of Organization in the development of Communication Studies at Faculty of Social and Politic Science, Raden Fatah Islamic State University . The methodology used in this research is descriptive, with qualitative approach. The theory for this research is using organizational information theory from karl Weick. The researcher will do observation, interview, guidelines, and documentation. Data collection techniques are primary data and secondary data. The data collection technique in this research is using primary data in the form of interview data from informants that were considered relevant and become the main source in this reserch, then secondary data that use official records such as documentations, books, etc. Data reduction, data presentation, and conclusions is used for data analysis techniques. The theory used is organization information. System is the absolute form (structure). Communication is a message delivered from the communicator to the communicant through verbal or writings then the occurrence of feedback. Organizations are a number of individuals organized to achieved certain goals. The organizational communication system used by Communication Study Program is a star pattern. Communication is carried out by not only work hour, but also the familiarity outside woring hoursthey do. The media which are used such as whatsapp, email, instagram, telephone, or in person. Barriers that occur are the lack of employess in updating information through online media, language, and distances. Communicaton between the employees occur in openness and good relationships are established. Communication that occurs is very positive. All stakeholders in the Communication Study Program, Faculty of Social and Politic Science are very open with staffs, lectures, and students.